Single-Atom Catalysts Dispersed on Graphitic Carbon Nitride (g-CN): Eley–Rideal-Driven CO-to-Ethanol Conversion - Jing Wang; Qiuli Song; Yongchen Shang; Yuejie Liu; Jingxiang Zhao (Nanomaterials, 2025)
The electrochemical reduction of carbon monoxide (COER) offers a promising route for generating value-added multi-carbon (C2+) products, such as ethanol, but achieving high catalytic performance remains a significant challenge. Herein, we performed comprehensive density functional theory (DFT) computations to evaluate CO-to-ethanol conversion on single metal atoms anchored on graphitic carbon nitride (TM/g–CN). We showed that these metal atoms stably coordinate with edge N sites of g–CN to form active catalytic centers. Screening 20 TM/g–CN candidates, we identified V/g–CN and Zn/g–CN as optimal catalysts: both exhibit low free-energy barriers (<0.50 eV) for the key *CO hydrogenation steps and facilitate C–C coupling via an Eley–Rideal mechanism with a negligible kinetic barrier (~0.10 eV) to yield ethanol at low limiting potentials, which explains their superior COER performance. An analysis of d-band centers, charge transfer, and bonding–antibonding orbital distributions revealed the origin of their activity. This work provides theoretical insights and useful guidelines for designing high-performance single-atom COER catalysts.